Game·Tel: An approach to multi-format and multi-device accessible engineering education - Anido, Luis; Burgos, Daniel; Caeiro, Manuel; Torrente, Javier; Fernández, Manuel; González, Javier; ...et al. (2011 Frontiers in Education Conference (FIE), 2020)
Game·Tel is an open source software system that supports personalized learning, focusing on serious games and simulations, making these and traditional content accessible and adaptive to the student and educational context. In this paper we discuss about its design and functionalities, its modular architecture and the multi-environment approach.
Keywords: games; TV; adaptation models; visualization; least squares approximation; computational modeling; engines; WOS(2); Scopus(2)